Analisa Lintasan Robot Mekanisme Paralel Planar 3R - Eka Setia Wahyudi; Syafri Syafri; Anita Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Robots are tools that can help alleviate human work [1]. Robots also have more functions than humans, such as having a high level of accuracy, have speed in completing the work, can do repetitive work in large quantities, and can reduce the cost of production. In this research, we evaluated the singular condition of a 3-dof RRR parallel robot prototype in order to have a trajectory planning in accordance with the design result. The trajectory Planning is done by considering kinematic constants by using the parameter of DH method and the Jacobi matrix. From the test results, the workingspace area that can be used for trajectory 3R parallel mechanism is in the range of 280 mm in the direction of X axis, 225 for mm Y axis direction, 240 mm in the direction of A and 215 mm for axis direction of the axis B.Keywords : Trajectory Planning, Parallel Mechanism, Parallel Robot, Workingspace, Singularity